Value Judgments in Health Inequality Measurement - Wagstaff, Adam (Wolters Kluwer Health, Inc., 2016)
Value judgments lurk beneath the surface in any study of health inequalities; analysts sought to understand them, make them explicit, and present results transparently to policymakers so that they, rather than analysts, decide which set of value judgments should be invoked. That is the key message of the paper “Lies, Damned Lies, and Health Inequality Measurements” by Gustav Kjellsson, Ulf-G Gerdtham, and Dennis Petrie. In this Commentary, the author offers some thoughts on, and practical suggestions regarding, the two interrelated issues highlighted by Kjellsson et al. (absolute vs. relative inequality; and the mirror issue). In so doing, he uses their valuable article as a springboard.